8PSAFETY OF IMPRIME PGG, A NOVEL INNATE IMMUNE MODULATOR, IN ADULTS WITH STAGE IV NON-SMALL CELL LUNG CANCER (NSCLC). (November 2014) - Thomas, M.; Schneller, F.; Sadjadian, P.; Hao, Z.; Mattson, P.; Lowe, J.; Huhn, R.; Braun, A.; Taitt, C.
Abstract : Background : Imprime PGG (IPGG; beta-1, 3/1, 6 glucan), a yeast-derived pathogen-associated molecular pattern (PAMP) primes innate immune cells to kill cancer cells opsonized by therapeutic antibodies. Recent results from an open-label randomized phase 2 trial in the frontline treatment of stage IV NSCLC showed significantly improved objective response rates (ORR; 48% vs 23%) with the addition of IPGG to backbone treatment with carboplatin, paclitaxel (C, P) and cetuximab (cet) versus same backbone treatment alone. Unplanned analyses by anti-beta glucan antibody (ABA) status, an independently established biomarker indicative of an individual's ability to respond to IPGG, showed further improved ORR (67%) and a trend towards improved survival (HR = 0.70; p = NS) with IPGG. Here we report for the first time detailed safety analyses from that trial. Results : A total of 88 patients (pts) were enrolled (59 IPGG, 29 control [ctl]) and evaluable for safety. All pts experienced at least 1 treatment-emergent adverse event (AE) over the course of the study. Grade (Gr) III/IV AEs occurred in 78.0 and 86.2% of pts, and serious AEs in 62.7 and 41.4%, respectively. Most common Gr III/IV AEs (occurring in at least 10% of pts) included neutropenia (32.2%, 48.3%), leukopenia (15.3%, 31%), and rash (3.4%, 10.3%). In the IPGG arm, 52.5% pts experienced Gr III/IV AEs reported as unlikely, possibly, or probably related to IPGG. Grade III/IV AEs related to cet were experienced by 55.9% pts in the IPGG group and 69.0% in the ctl group, and Gr III/IV AEs related to C, P by 66.1% and 65.5%, respectively. Two subjects in the IPGG group (neutropenia, sepsis and acute renal failure considered unlikely related to IPGG; pleural effusion considered unrelated to IPGG in 1 pt each) and 0 in the ctl group died due to AEs. Results by biomarker subsets will be presented. Conclusions : IPGG was generally well tolerated in pts with stage IV NSCLC receiving C, P and cet therapy frontline. Disclosure : P. Mattson, J. Lowe, R. Huhn, A. Braun and C. Taitt: I am an employee of Biothera and have stock options and/or grants as part of the employee stock plan. All other authors have declared no conflicts of interest.